1952
DOI: 10.1139/z52-021
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Performance of the Precipitin Test in the Determination of Blood Meals of Insects

Abstract: Certain factors influence the performance of precipitin tests when the latter are used for detection of blood meals of biting flies. Antisera stored in a liquid state in a refrigerator generally show a decrease in titer with the passage of time. Aging appears to have an adverse effect on the avidity of an antiserum. Smears of blood-engorged mosquitoes prepared by smearing of the entire insect are satisfactory for testing by the precipitin reaction. A high-titered antiserum which can be diluted is desirable for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1954
1954
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 5 publications
1
8
0
Order By: Relevance
“…Similar results were obtained when the serially diluted blood was tested directly without being absorbed on and eluted from filter paper, thus showing that Eligh's (1952) concern that some proteins may be irreversibly absorbed to filter paper is unfounded in this instance. Detection period Host identification is supposed to be performed on relatively freshly blood-engorged mosquitoes, but in practice it is often desirable to be able to identify blood-meals from insects that have digested much of the blood.…”
Section: Sensitivitysupporting
confidence: 67%
“…Similar results were obtained when the serially diluted blood was tested directly without being absorbed on and eluted from filter paper, thus showing that Eligh's (1952) concern that some proteins may be irreversibly absorbed to filter paper is unfounded in this instance. Detection period Host identification is supposed to be performed on relatively freshly blood-engorged mosquitoes, but in practice it is often desirable to be able to identify blood-meals from insects that have digested much of the blood.…”
Section: Sensitivitysupporting
confidence: 67%
“…Several methods of collecting and storing predators have been used. A very convenient method, which allows easy transport of material, is to smear the gut contents onto filter paper, but it is known that proteins tend to bind to cellulose and it may be difficult to elute all the protein if the samples are stored for long periods (Eligh, 1952). Good quality paper such as Whatman No.…”
Section: Collection and Preparation Of Predatorsmentioning
confidence: 99%
“…The sensitivity of the latex agglutination test was slightly less than that of the precipitin test. The method of extraction of blood-meals, as used here, has little effect on the sensitivity of the test, but it has been shown that under certain circumstances some protein is 'bound to filter paper and cannot toe eluted (Eligh, 1952). When attempts to isolate viruses are to be undertaken, it will toe necessary to use whole insects rather than squashes, since this is less likely to cause denaturation of the virus.…”
Section: Discussionmentioning
confidence: 99%